Interrelationships Between Ovarian Dynamics and Blood Plasma Profile in Double Ovsynch Treated Jaffrabadi Heifers and Buffaloes - Raval, Rupesh J.; Dhami, Arjun J.; Kavani, Fulabhai S.; Vijyeta, Hardeep P. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
A study was carried out on post-pubertal acyclic Jaffrabadi buffalo heifers (n = 12, age 40-50 months) and >90 days postpartum lactating  acyclic buffaloes (n = 6) employing double Ovsynch protocol to evaluate the treatment response, ovarian dynamics, and hormonal and  biochemical profile assessed on different days of treatment till day 35 post-FTAI and their correlations. The protocol consisted of i/m  injections of 20 µg Buserelin acetate, a GnRH analogue on day 0, 10, 17 and 26, and 500 µg PGF2α, Cloprostenol, on day 7 and 24, with  a timed insemination on day 27. The populations of small (4 mm), medium (4-8 mm) and large (>8 mm) size follicles, and the diameters  of largest/ dominant and subordinate follicles did not vary between double Ovsynch treated acyclic heifers and buffaloes, but they  were significantly (p
Keywords: Biochemical profile; Correlations; Double Ovsynch; Hormonal profile; Jaffrabadi buffalo; Ovarian dynamics